On one mathematical problem in the theory of nonlinear oscillations - Grebenikov, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We consider one mathematical problem that was discussed by the author and A. M. Samoilenko at the Third International Conference on the Theory of Nonlinear Oscillations (Transcarpathia, 1967).